The Effects of Capability and Social Interaction on Job Performance, with Organizational Citizenship Behavior as a Moderasi a Study at the Islamic Hospital in Magelang City - Aditya Angger Wibowo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
This study aims to investigate the determinants of job performance by integrating the variables of capability, social interaction, and Organizational Citizenship Behavior (OCB) as a moderating variable. The phenomenon of employee turnover and discrepancies in staff discretionary behavior within the hospital setting serves as the primary rationale for this study. Using a quantitative approach, data were collected from 240 respondents at Magelang City Islamic Hospital through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) based on AMOS software to test the causal relationships among variables in the structural model. The research findings provide empirical confirmation that individual capabilities and the quality of social inter-actions have a positive and significant influence on stimulating the formation of OCB. Furthermore, statistical test results demonstrate that capabilities, social interactions, and OCB simultaneously make a significant contribution to improving employee work performance. The presence of OCB is identified as a crucial factor capable of strengthening organizational performance outcomes. The practical implications of this study emphasize the need for hospital management to formulate human resource development strategies focused on strengthening technical skills and social cohesion to mit-igate the impact of turnover and accelerate the sustainable performance of healthcare services.